Social Interactions, Mechanisms, and Equilibrium: Evidence from a Model of Study Time and Academic Achievement - Tim Conley; Nirav Mehta; Ralph Stinebrickner; Todd Stinebrickner (Center for Economic Studies and ifo Institute (CESifo), 2018)
We develop and estimate a model of student study time on a social network. The model is designed to exploit unique data collected in the Berea Panel Study. Study time data allow us to quantify an intuitive mechanism for academic social interactions: own study time may depend on friend study time in a heterogeneous manner. Social network data allow us to embed study time and resulting academic achievement in an estimable equilibrium framework. We develop a specification test that exploits the equilibrium nature of social interactions and use it to show that novel study propensity measures mitigate econometric endogeneity concerns.
Keywords: C52; C54; I20; 330; social networks; peer effects; homophily; time-use